The virtual kidnapping of youth by social media advertising - Marie Leiner; Jose Manuel de la Rosa; Cecilia de Vargas (Journal of Pediatric and Neonatal Individualized Medicine, 2024)
The scholarly discourse presented in this document meticulously dissects the intricate phenomenon of “virtual kidnapping” orchestrated by social media advertising. Adolescents are metaphorically ensnared in the digital realm, distanced from genuine interactions and caught in a web of detrimental consequences spanning their mental well-being, social integration, and cognitive development. The evolution of media influence from conventional platforms to the digital domain has heralded a transformative shift toward tailored content dissemination, algorithmic advertising methodologies, and ethical dilemmas surrounding the delineation between manipulation and persuasion in targeting susceptible youth. This article expounds on the deleterious effects of excessive television and social media exposure on young individuals, accentuating its disruptions of sleep patterns, cognitive abilities, physical health, academic attainment, and interpersonal skills. The comparative analysis of marketing practices in television versus social media unveils regulatory disparities and challenges in shielding minors from precision-targeted marketing tactics prevalent in the digital sphere. Moreover, the profound impact of social media on adolescent mental health is rigorously scrutinized, attributing escalating rates of psychological distress, anxiety disorders, and suicidal behavior to constant digital connectivity, pervasive comparison culture, and exposure to unattainable body standards. This discourse underscores the need for heightened awareness, robust regulatory frameworks, and conscientious media consumption practices to fortify the comprehensive well-being of young individuals amidst the burgeoning digital landscape, advocating for a holistic reassessment of media’s pivotal role in shaping youth development.